La violencia sexual como una forma de tortura en el derecho internacional de los derechos humanos - Núñez Marín, Raúl Fernando (2023)
Sexual violence has been defined by different organizations and international courts as a form of torture, because of the serious consequences that this behavior has on victims. This international standard imposes specific obligations on states. These obligations must be met in the domestic proceedings, in order to fully protect the human rights of victims in light of the international law of human rights.